2022
DOI: 10.1177/20406223211063059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonsurgical, minimally or noninvasive therapies for urinary incontinence due to neurogenic bladder: a systematic review and meta-analysis

Abstract: Objective: To determine the effects of nonsurgical, minimally or noninvasive therapies on urge urinary incontinence (UUI) symptoms and quality of life (QoL) in individuals with neurogenic bladder (NGB). Data Sources: Cochrane library, EMBASE, MEDLINE, PEDro, Scopus, and Web of Science databases were searched from inception to September 2021. Review Methods: Randomized controlled trials that compared therapies such as intravaginal electrical stimulation (IVES), transcutaneous electrical nerve stimulation (TENS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Screening the titles and abstracts, left us with 76 studies which were selected for full‐text screening. Finally, 20 SRs met all the inclusion criteria and entered the study 16–35 . The PRISMA flow diagram of the literature search and results is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Screening the titles and abstracts, left us with 76 studies which were selected for full‐text screening. Finally, 20 SRs met all the inclusion criteria and entered the study 16–35 . The PRISMA flow diagram of the literature search and results is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 20 SRs, 13 of them conducted meta‐analysis 16,17,19,20,23,24,27,29,31–35 . China was the leading origin of publication with five studies 16,31–34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis revealed that daily transcutaneous electrical nerve stimulation (TENS) and electroacupuncture at least 5 days per week starting less than 3 months post-stroke may be effective for treating urinary incontinence ( Cruz et al, 2021 ). Another meta-analysis found that TENS may reduce the severity of urinary incontinence ( Thomas et al, 2019 ) and that both TENS and neuromuscular electrical stimulation can reduce symptoms of post-stroke urge incontinence ( Ali et al, 2022 ). One study showed that repetitive 5-Hz transcranial magnetic stimulation (rTMS) to the motor cortex was useful to facilitate the voiding phase in patients with multiple sclerosis ( Centonze et al, 2007 ).…”
Section: Treatmentsmentioning
confidence: 99%